A study of a wind catcher assisted adsorption cooling channel for natural cooling of a 2-storey building. (1st May 2016) - Haghighi, A.P.; Pakdel, S.H.; Jafari, A.
Abstract: This study proposes a new system composing of a wind catcher and a solar driven two-bed silica gel–water adsorption chiller in order to provide natural cooling of a two-story building. The wind catcher provides the required ventilation, and the air flowing though the wind catcher is cooled by the cooling plates fed by the adsorption chiller. The performance of the system is studied theoretically under different ambient conditions such as wind velocity, solar radiation, air temperature and relative humidity. In addition, the influence of geometric parameters such as size of the apertures, wind catcher's height and dimensions of the cooling plates and the number of them are studied. Furthermore, the system's capability to provide thermal comfort in the living space is investigated. It is found that at lower ACH (air change per hour) values, inlet air's temperature and absolute humidity reduce more. In addition, with the rise of the cooling plates' length, the cooling effect increases. The results indicated that with the increase of ACH values, thermal comfort condition is achieved for larger cooling demands. Furthermore, the system was found to be able to cool the air between 10 and 20 °C under different ambient conditions. Highlights: A new system consisting of a wind catcher and a solar adsorption chiller is proposed. The values of ACH were compared under different geometrical parameters. With the increase of ACH, thermal comfort can be achieved for larger cooling demands. Thermal comfort is achieved for a maximum of 2200 W cooling demand in a 50 m 3 room. Application of the system is found to be beneficial in hot and humid climates.